AI-Driven Predictive Analytics and Intelligent Automation in Modern Banking: A Comprehensive Framework for Risk Management and Financial Forecasting - Uttama Reddy Sanepalli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The banking sector faces unprecedented challenges in managing complex financial operations, detecting fraud, assessing credit risks, and ensuring regulatory compliance in an increasingly digital ecosystem. Traditional rule-based systems and statistical models struggle to process vast volumes of heterogeneous data in real-time while maintaining accuracy and adaptability. This research presents a comprehensive framework that integrates artificial intelligence and machine learning techniques with microservices architecture, cloud-native technologies, and advanced predictive analytics to transform core banking operations. The proposed solution addresses critical gaps in existing approaches by implementing adaptive federated learning systems, AI-augmented threat intelligence mechanisms, and cognitive security frameworks that enable distributed processing while maintaining data privacy and security. Through the deployment of serverless intelligence architectures and real-time feature engineering pipelines, the framework achieves significant improvements in fraud detection accuracy (94.7%), credit risk assessment precision (92.3%), and operational efficiency (87% reduction in processing time). Experimental validation demonstrates the framework's capability to handle multi-regulatory environments, automate vulnerability management in cloud-native clusters, and provide proactive cybersecurity measures. The integration of policy-as-code enforcement and zero-trust automation ensures secure deployments while maintaining compliance across distributed banking systems. This research contributes a scalable, secure, and adaptive solution that modernizes financial forecasting, enhances customer experience, and establishes a foundation for autonomous banking operations in the digital age.
Keywords: Artificial Intelligence; Machine Learning; Banking Systems; Predictive Analytics; Microservices Architecture; Cloud-Native Security; Federated Learning